2016
DOI: 10.1021/acs.jpcc.6b01549
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity Control in Palladium-Catalyzed Alcohol Oxidation through Selective Blocking of Active Sites

Abstract: stabilized metal nanoparticles (NPs) have received wide interest in a number of liquid-phase catalytic transformations but the role of the capping/protective agent is still debated . Operando attenuated total reflection infrared (ATR-IR) spectroscopy enabled us to obtain unprecedented molecular level insights into the selectivity issue induced by the presence of the protective agent by following the liquid-phase benzyl alcohol oxidation on Pd/Al 2 O 3 . Supported Pd NPs protected by polyvinylalcohol (PVA) show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 40 publications
1
59
0
Order By: Relevance
“…Supported Pd nanoparticles were synthesized by the sol-immobilization method [27]. Two aqueous solutions, one containing the metal precursor (Na 2 PdCl 4 , 1 mL of a 1.26 × 10 −4 mol L −1 solution) and one containing the desired capping agent (1 mL of a 1 wt % solution, capping agents/Pd (w/w) = 1), were added to 100 mL of deionized water.…”
Section: Catalysts Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Supported Pd nanoparticles were synthesized by the sol-immobilization method [27]. Two aqueous solutions, one containing the metal precursor (Na 2 PdCl 4 , 1 mL of a 1.26 × 10 −4 mol L −1 solution) and one containing the desired capping agent (1 mL of a 1 wt % solution, capping agents/Pd (w/w) = 1), were added to 100 mL of deionized water.…”
Section: Catalysts Preparationmentioning
confidence: 99%
“…It was also observed that supported Pd nanoparticles (NPs) protected by PVA led to higher selectivity to benzaldehyde in the liquid phase oxidation of benzyl alcohol, despite the conversion being lower. This was mainly because of the preferential blocking of Pd (111) facets, which have been recognized to facilitate the decarbonylation process [27]. Indeed, Rogers et al proposed that the interaction between the solvent and PVA alters the PVA binding on the metal surface.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Campisi et al [68] ascribed the improved selectivity in benzyl alcohol oxidation to the presence of PVA on Pd NPs. Investigating the surface site accessibility through DRIFTS-monitored CO adsorption, they attributed the peculiar catalytic behaviour to the preferential blocking of Pd(111) facets, which have been recognized to promote the decarbonylation process [69] by residual PVA (Figure 7).…”
Section: Shielding Effect and Selective Blockingmentioning
confidence: 99%
“…Generally, it is considered that the activity is a compromise between particle size of the metal and the shielding effect of the PVA ligand . However, in the case of these catalysts the shielding effect did not seem to contribute, either because the maximum amount of PVA used in these catalyst preparations was below the amount required to cause this effect, there is good diffusion of the glucose through the PVA layer, or the PVA is removed under reactions conditions, an effect that we have reported previously .…”
Section: Resultsmentioning
confidence: 50%